Psycho-juridical of the traditional oil mining in the Wonocolo village, Kedewan, Bojonegoro, East Java - Agoes Dariyo (Psychology Study Program, Faculty of Medicine, Universitas Lambung Mangkurat, 2020)
Oil is a commercial commodity that benefits a country, including Indonesia. During this time, oil mining activities carried out by Pertamina using modern machinery. However, there are still oil mining activities carried out by the people using traditional machines.This study focuses on a psycho-juridical review of traditional oil mining that has been carried out from generation to generation by ancestors and continues to this day in the village of Little Texas Wonocolo, Kedewan, Bojonegoro, East Java. Retrieval of data using interviews, observation and documentation. The study involved 5 subjects who knew about the problems of oil mining in the Wonocolo village area. Data analysis using the triangular approach. The results showed that the Wonocolo villagers conducted oil mining based on 3 factors, namely the uniqueness of geographical areas, customary law factors inherited orally and in writing and economic motive factors. Furthermore, the results of the study are discussed in this paper.